Spontaneous Vulvar Hematoma in Pregnancy: A Case Report - Shrestha, Salina; Shrestha, Salina; Lama, Jyoti Bhaju; Neupane, Sujata Khadka; Mahato, Suruchi; Gurung, Saraswati (Medical Journal of Eastern Nepal, 2024)
Spontaneous vulvar hematoma is a rare occurrence during pregnancy but can be seen as an uncommon complication of childbirth or may present after traumatic injury. Here we present a case of a 19-year-old female with a vulvar hematoma who presented with complaints of vulvar swelling and pain with no preceding traumatic event at 32 weeks of pregnancy. The diagnosis was made through physical examination and radiological evaluation. Due to increasing size and unbearable pain, surgical evacuation of the hematoma along with blood transfusion was done. The postoperative period was uneventful, vulval swelling resolved, and she was discharged on the 4th postoperative day.